Paths in remnant movement: A single solution to three problems in the Polish OVS syntax - Wiland, Bartosz (GLSA: Amherst, Massachusetts, 2013)
On the one hand it has been advanced that remnant movement (RM) serves as a replacement for head movement and leads to certain permutations in word order while it disallows some others (e.g. Cinque (2005)), on the other hand, little attention has been devoted to the consequences RM has for clausal syntax. In this work, I illustrate one such consequence, namely the rise of crossing and nesting movement dependencies and their reflexes. In particular, I make a case for the existence of massive RM that involves entire clausal subtrees in Polish. The analysis provides a uniform solution to three robust puzzles in the Polish OVS construction in a straightforward way.